The Possible Role of Hypothalamus-Pituitary-Adrenal Dysfunction in Epileptic Spasms. (October 2020) - Peng, Bing-Wei; Li, Xiao-Jing; Wu, Wen-Xiao; Zeng, Yi-Ru; Liao, Yin-Ting; Hou, Chi; Liang, Hui-Ci; Zhang, Wen; Wang, Xiu-Ying; Chen, Wen-Xiong
Highlights: A possible link between cortisol rhythm and the circadian rhythm in ES has been identified. The study results hint the HPG axis dysfunction in ES. Further validation of the study results can lead to the development of newer therapeutics for ES. Abstract: Purpose: To analyze diurnal cortisol (COR) rhythms among children with epileptic spasms (ESs) and explore the relationship between endocrine factors, circadian rhythm, and ES. Methods: This study assessed the COR and adrenocorticotropic hormone (ACTH) levels at 08:00 and 16:00, and COR values at 00:00 among children with ESs. Additionally, the etiology of ESs was analyzed. All cases were divided into the following three etiology groups: genetic group, structural etiology group, and unknown etiology group. ACTH was administered to 24 patients, who were divided into the positive electroclinical outcome group and negative electroclinical outcome group. All data were analyzed using a two-way repeated measures analysis of variance. Results: All children showed a COR rhythm. Controls displayed a significantly different COR rhythm from that in the ES group (Fgroup*COR =24.100, p = 0.000). It was observed that the ACTH levels at 08:00 (t = −3.720) and 16:00 (t=-3.794) and COR levels at 16:00 (t = −2.264) and 00:00 (t = −4.607) in the ES group were significantly higher than those in the control group (p < 0.05); COR levels at 08:00 were significantly lower among individuals in the structural etiology group (F = 3.828, p < 0.05). COR levels at 08:00 in the negative electroclinical outcome group (668.30 ± 227.42) nmol/L were higher than those in the positive electroclinical outcome group (462.25 ± 249.71) nmol/L. Conclusion: Our results suggest that the change in COR rhythm is an important pathophysiological characteristic of ESs, suggesting that hypothalamus-pituitary-adrenal axis dysfunction possibly leads to the different manifestations of ESs.